The approaching of adolescents in groups in the context of the education in health and sexually transmitted diseases prevention: o contexto da educação em saúde e prevenção de DST - Souza, Márcia M.; Borges, Ida K.; Medeiros, Marcelo; Teles, Sheila A.; Munari, Denize B. (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction: the sexually transmitted diseases (STD) are among the most often Public Health problems on the whole world. Last decades, manyefforts have been done to prevention of these diseases mainly to youth population. Health Education constitutes STD prevention and control possibil-ity and, group activities generally are a good choice to work with youth clients. Objective:with paper we sough to debate about some adolescentgroup approach characteristics on Health Education activities to STD prevention. Method: review paper developed from a non exhausted literaturereviewing comparison to researchers work experiences with adolescents, considering youth vulnerability to STD. Results: as results emerged fromdiscussion three categories focused on adolescence and on vulnerability to STD; on adolescent needs and Health Education; and on group discussionmanaging through its context. Conclusion: we conclude that group as strategy to approaching adolescents is very appropriate, because its possibili-ties to offer dynamic conditions close to reality and adolescent way of life characteristics. However, it is necessary to health professionals a basicknowledge about group movements and its dynamics, because planning interventions to the group isn’t enough, but with the members group partici-pation.